2020
DOI: 10.1002/nau.24312
|View full text |Cite
|
Sign up to set email alerts
|

Is polypropylene mesh material fundamentally safe for use as a reconstructive material in vaginal surgery: ICI‐RS 2019?

Abstract: Polypropylene (PP) mesh has been used as a primary or adjuvant material for vaginal reconstruction for both stress urinary incontinence (SUI) and pelvic organ prolapse (POP) for decades. Whether polypropylene is the optimal material for such indications has been called into question by clinicians, regulatory agencies and the public in several countries around the world. This paper is a report of presentations and subsequent discussion at the annual International Consultation on Incontinence Research Society (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Lighter, more porous and less stiff PP meshes have been reported to have a less negative impact on the metabolism of both collagen and elastin when compared with normal weight PP mesh. 29 PVDF has advantageous physiochemical and handling characteristics. Recent studies have shown the potentially favorable tissue reaction and biocompatibility of PVDF as a mesh material for pelvic floor repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lighter, more porous and less stiff PP meshes have been reported to have a less negative impact on the metabolism of both collagen and elastin when compared with normal weight PP mesh. 29 PVDF has advantageous physiochemical and handling characteristics. Recent studies have shown the potentially favorable tissue reaction and biocompatibility of PVDF as a mesh material for pelvic floor repair.…”
Section: Discussionmentioning
confidence: 99%
“…New materials are being considered. Lighter, more porous and less stiff PP meshes have been reported to have a less negative impact on the metabolism of both collagen and elastin when compared with normal weight PP mesh 29 . PVDF has advantageous physiochemical and handling characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Erst mit der Einführung des TVT ("tension free vaginal tape") durch Ulmsten et al [3] verbreitete sich ein günstiges und leicht zu verarbeitendes Material (Polypropylen), dessen Eigenschaften (Typ-1-Mesh nach Amid: monofilamentär, makroporös, leichtgewichtig, weich) den bis dahin verwendeten überlegen war. Aktuell wird das Polypropylen bei genauerer struktureller, mikrobiologischer und immunologischer Betrachtung als Standardmaterial der Beckenbodenchirurgie wieder kontrovers gesehen [20].…”
Section: Alloplastische Bänderunclassified
“…The results obtained with PP are less consistent than other materials and have a variety of weakness in layer adhesion and general adhesion to the bed of the printer as could be observed throughout the print process of our cylinders. Furthermore, even though PP shows clinical benefits, such as its flexibility and tenacity, very useful in operations like hernia repairs and pelvic organ prolapse surgery [35,36], recent studies show that implants made with this material might cause a reaction in the body's immunologic system [30] and therefore we are concerned about possible implications derived from even a short term exposure to this material.…”
Section: Materials Strength Assessmentmentioning
confidence: 99%